Reconceptualizing Qiwāmah: Gender-Responsive Exegesis and Relational Authority In Contemporary Muslim Families - Anisa, Lina Nur (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2026)
The concept of qiwāmah in Islamic tradition has often been associated with male authority within a patriarchal marital structure, an interpretation that insufficiently captures the relational transformations of contemporary Muslim families. This study reconceptualizes qiwāmah in marital relations through an integrative framework that combines gender-responsive Qur’anic exegesis with insights from Muslim family psychology. Using qualitative library research, it synthesizes scholarship on gender hermeneutics, Islamic family law, and contemporary family dynamics to examine how interpretations of male leadership shape relational authority, role negotiation, and family well-being. The findings indicate that qiwāmah is better understood as a relational construct grounded in responsibility and negotiated leadership rather than hierarchical domination. Its reinterpretation aligns with partnership-based roles, dialogical communication, and shared accountability, contributing to perceptions of relational justice and psychological well-being. This study advances a relational framework of qiwāmah that bridges normative Islamic discourse with contemporary family psychology, offering both theoretical contributions and practical implications for counseling, premarital education, and family development in modern Muslim contexts.